Impact of Effective Viscosity on Blood Flow through Sinusoidal Stenosed Curved Artery - Pokharel, Chudamani; Kafle, Jeevan; Bhatta, Chet Raj (Journal of Nepal Mathematical Society, 2024)
Atherosclerosis induced narrowing of arteries reduces blood flow to critical regions, contributing to conditions such as ischemia, angina, and strokes. Curvature is observed in blood vessels at various locations. The sinusoidal stenotic surface provides additional curvature and a point of maximum shear, which varies with the cross-section. This research extends the cylindrical form of the Navier-Stokes equations in a polar coordinate system to incorporate effective viscosity and axial curvature, enabling the analysis of blood flow behavior in curved arteries with sinusoidal stenosis. The blood flow behavior was studied by taking different blood parameters using an extended blood flow model. Moreover, aspects of blood flow such as velocity profile, volumetric flow rate, pressure drop, and shear stress have been studied in relation to blood flow around curved arteries with sinusoidal stenosis, variations in the radii of the artery, thickness of the stenosis, hematocrit, and viscosity. The findings reveal that increasing the values of curvature, hematocrit, viscosity, and thickness of stenosis can quickly reduce velocity and volumetric flow rate while amplifying shear stress and pressure drop. This research considers flow conditions consistent with prior studies and opens routes for exploring unsteady and three-dimensional effects in similar geometries.